CO2 induced seawater acidification impacts survival and development of European eel embryos - Daniela E. Sganga; Flemming T. Dahlke; Sune R. Sørensen; Ian A. E. Butts; Jonna Tomkiewicz; David Mazurais; Arianna Servili; Francesca Bertolini; Sebastian N. Politis (PLoS ONE, 2022)
Fish embryos may be vulnerable to seawater acidification resulting from anthropogenic carbon dioxide (CO2) emissions or from excessive biological CO2 production in aquaculture systems. This study investigated CO2 effects on embryos of the European eel (Anguilla anguilla), a catadromous fish that is considered at risk from climate change and that is targeted for hatchery production to sustain aquaculture of the species. Eel embryos were reared in three independent recirculation systems with different pH/CO2 levels representing “control” (pH 8.1, 300 μatm CO2), end-of-century climate change (“intermediate”, pH 7.6, 900 μatm CO2) and “extreme” aquaculture conditions (pH 7.1, 3000 μatm CO2). Sensitivity analyses were conducted at 4, 24, and 48 hours post-fertilization (hpf) by focusing on development, survival, and expression of genes related to acute stress response (crhr1, crfr2), stress/repair response (hsp70, hsp90), water and solute transport (aqp1, aqp3), acid-base regulation (nkcc1a, ncc, car15), and inhibitory neurotransmission (GABAAα6b, Gabra1). Results revealed that embryos developing at intermediate pH showed similar survival rates to the control, but egg swelling was impaired, resulting in a reduction in egg size with decreasing pH. Embryos exposed to extreme pH had 0.6-fold decrease in survival at 24 hpf and a 0.3-fold change at 48 compared to the control. These observed effects of acidification were not reflected by changes in expression of any of the here studied genes. On the contrary, differential expression was observed along embryonic development independent of treatment, indicating that the underlying regulating systems are under development and that embryos are limited in their ability to regulate molecular responses to acidification. In conclusion, exposure to predicted end-of-century ocean pCO2 conditions may affect normal development of this species in nature during sensitive early life history stages with limited physiological response capacities, while extreme acidification will negatively influence embryonic survival and development under hatchery conditions.